2011
DOI: 10.2527/jas.2010-3563
|View full text |Cite
|
Sign up to set email alerts
|

Effects of roughage source and distillers grain concentration on beef cattle finishing performance, carcass characteristics, and in vitro fermentation1,2

Abstract: Two experiments were conducted to evaluate the effects of wet distillers grains plus solubles (DG) and roughage source on finishing cattle performance, carcass characteristics, and in vitro fermentation. In Exp. 1, crossbred beef steers (n=224, initial BW=349 kg) were used in a randomized complete block design with a 2 × 3 + 1 factorial arrangement of treatments. Experimental diets were a standard steam-flaked corn (SFC)-based control (no DG and 10% alfalfa hay), and either 15 or 30% DG (DM basis) with roughag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 17 publications
2
17
1
Order By: Relevance
“…Treatment effects on growth performance and dietary NE values are shown in Table 6. Consistent with previous studies evaluating DDGS substitution for SF corn in cross-bred beef breeds (Gordon et al, 2002;Uwituze et al, 2010;Quinn et al, 2011), there were no treatment effects (P ≥ 0.56) on DMI in calf-fed Holstein steers. During the initial 126-d period, when metabolizable AA supply is expected to be most limiting (NRC, 2000), increasing level of DDGS linearly increased (P = 0.03) ADG and increased quadratically (P ≤ 0.03) G:F, dietary NE, and observed/expected diet NE, with the response being maximal at 20% DDGS inclusion rate.…”
Section: Methodssupporting
confidence: 89%
“…Treatment effects on growth performance and dietary NE values are shown in Table 6. Consistent with previous studies evaluating DDGS substitution for SF corn in cross-bred beef breeds (Gordon et al, 2002;Uwituze et al, 2010;Quinn et al, 2011), there were no treatment effects (P ≥ 0.56) on DMI in calf-fed Holstein steers. During the initial 126-d period, when metabolizable AA supply is expected to be most limiting (NRC, 2000), increasing level of DDGS linearly increased (P = 0.03) ADG and increased quadratically (P ≤ 0.03) G:F, dietary NE, and observed/expected diet NE, with the response being maximal at 20% DDGS inclusion rate.…”
Section: Methodssupporting
confidence: 89%
“…Analysis of acid insoluble ash, total starch, N, and OM were conducted on samples of diets, orts, and feces collected during the digestion phase as described by Ponce et al (2013). Neutral detergent fiber was determined using an Ankom 200 Fiber Analyzer (Ankom Technology, Macedon, NY) as described by Quinn et al (2011). Apparent total tract digestion of DM, OM, CP, NDF, and starch was calculated as follows: 100 -100 × [(AIA concentration in feed/AIA concentration in feces) × (nutrient concentration in feces/nutrient concentration in feed)].…”
Section: Laboratory Analysesmentioning
confidence: 99%
“…This suggests that feeding a balanced amount of starch and fiber in a supplement may provide the additional energy boost without decreasing rumen function and fiber utilization. in these studies (Uwituze et al, 2010;Quinn et al, 2011) suggest that roughage eNDF should also be taken in consideration when selecting roughage source to include in high concentrate diets. In a literature analysis conducted by , the data support the recommendations of Quinn et al (2011) and indicated that eNDF described the change in DMI more completely than total NDF.…”
Section: Negative Associative Feed Effectsmentioning
confidence: 99%
“…in these studies (Uwituze et al, 2010;Quinn et al, 2011) suggest that roughage eNDF should also be taken in consideration when selecting roughage source to include in high concentrate diets. In a literature analysis conducted by , the data support the recommendations of Quinn et al (2011) and indicated that eNDF described the change in DMI more completely than total NDF. However, suggested eNDF may not be a practical measure for producers and may only separate roughage differences for certain roughages.…”
Section: Negative Associative Feed Effectsmentioning
confidence: 99%
See 1 more Smart Citation